Vapor putty for special vehicle body material and preparation method thereof
By combining modified unsaturated polyester resin and modified talc powder, a new type of atomic ash was prepared, which solved the problems of harmful styrene, insufficient antibacterial performance and poor heat resistance of existing atomic ash, and achieved more High environmental protection, safety and durability performance.
Patent Information
- Application Number
- CN202411831305.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the application of existing atomic ash, there are problems such as styrene being harmful to the human body, insufficient antibacterial performance and poor heat resistance, which affects the safety and durability of the vehicle body.
Mixed and grinded with modified unsaturated polyester resin, modified talc powder, bentonite, vapor phase silica, titanium dioxide, cobalt isocitate, cyclohexanone peroxide and dibutyl phthalate, etc., and at high pressure Irradiated under a mercury lamp, atomic ash with improved performance was prepared.
It improves the heat resistance and antibacterial properties of atomic ash, reduces the use of styrene, enhances adhesion to metal substrates, and meets the higher requirements of special car body materials for environmental protection, safety and durability.
Smart Images

Figure BDA0005185617720000121 
Figure BDA0005185617720000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of atomic putty, in particular to an atomic putty used for special vehicle body materials and a preparation method thereof. Background Art
[0002] Putty, as a polymer filling material widely used in car body repair and decoration, is known for its excellent filling, adhesion and polishing properties. It is mainly composed of unsaturated polyester resin and filler, and is quickly cured by adding curing agent to form a hard and durable surface layer. However, putty also exposes some shortcomings in its application.
[0003] First, styrene, a commonly used cross-linking agent in putty, is harmful to the human body. Long-term contact or inhalation of styrene may cause damage to the nervous system, abnormal liver function, and increased risk of cancer. Therefore, it is necessary to reduce the use of this harmful substance while maintaining the excellent performance of putty; secondly, putty is prone to breed bacteria in a humid environment, causing surface contamination and deterioration of the material. The non-antibacterial properties not only affect the appearance of the car body, but may also pose a potential threat to the health of the occupants. In addition, the heat resistance of putty is also an aspect that needs to be improved. In a high temperature environment, the putty may deform, crack or fall off, affecting the durability and safety of the car body.
[0004] In summary, the application of putty in the field of body materials has not only demonstrated its unique advantages, but also exposed some shortcomings that need to be solved urgently. We can continue to work hard to improve the performance of putty by reducing the use of styrene, improving antibacterial properties and heat resistance, so as to meet the higher requirements of special body materials for environmental protection, safety and durability. Summary of the invention
[0005] The object of the present invention is to provide an atomic putty for special vehicle body materials and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The invention discloses an atomic putty for special vehicle body materials. The atomic putty for special vehicle body materials is obtained by mixing and grinding modified unsaturated polyester resin, dispersant, modified talcum powder, bentonite, fumed silica, titanium dioxide, cobalt isooctanoate, cyclohexanone peroxide and dibutyl phthalate, and then irradiating the mixture under a high-pressure mercury lamp.
[0008] Preferably, the modified unsaturated polyester resin is obtained by reacting a modified unsaturated polyester resin precursor obtained by reacting tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, and hydroquinone with a hydroxyl-terminated modified polysiloxane, and then reacting with isocyanate-based terpyridine.
[0009] Preferably, the modified talc is obtained by reacting talc modified with p-aminophenyltrimethoxysilane with chlorobenzene, cyclizing with sulfur powder, reacting with 1-iodoheptane, aldehydeizing with phosphorus oxychloride, and then grafting arginine.
[0010] A method for preparing putty for special vehicle body materials comprises the following preparation steps:
[0011] (1) Weighing bis(trichloromethyl) carbonate and 4-amino-2,2,6,2-terpyridine in a molar ratio of 1:3; mixing bis(trichloromethyl) carbonate and chlorobenzene in a mass ratio of 1:10 to obtain a bis(trichloromethyl) carbonate solution, and stirring at -5°C for 5-10 minutes; mixing 4-amino-2,2,6,2-terpyridine and chlorobenzene in a mass ratio of 1:10 to obtain a 4-amino-2,2,6,2-terpyridine solution; dropping the 4-amino-2,2,6,2-terpyridine solution into the bis(trichloromethyl) carbonate solution at a dropping rate of 1 mL / min, and stirring at -5°C for 30 minutes after the dropping, heating to 65-70°C and reflux reaction for 6-7 hours, and filtering after the reaction, washing with chloroform 4 times, and vacuum drying at 50°C for 12 hours to obtain isocyanate terpyridine;
[0012] (2) Tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol and hydroquinone are mixed, heated to 160° C., then heated at a rate of 10° C. / h to 190° C., reacted for 2 hours, and then vacuumed for 30 minutes. The reaction was continued until the acid value reached 60 mgKOH / g, then the temperature was lowered to 160° C., trimethylolpropane diallyl ether was added, and the reaction was continued until the acid value reached 40 mgKOH / g to obtain a modified unsaturated polyester resin precursor; the modified unsaturated polyester resin precursor was added to the modified unsaturated polyester resin precursor at a temperature of 160° C. The pre-modified unsaturated polyester resin was prepared by heating the pre-modified unsaturated polyester resin and styrene in a mass ratio of 1:0.05, heating the pre-modified unsaturated polyester resin and adding isocyanate terpyridine, heating the pre-modified unsaturated polyester resin to 80°C for reaction for 2h, adding ethylene glycol for reaction for 30min, and obtaining the unsaturated polyester resin after the reaction.
[0013] (3) Pretreated talc, sulfur powder, diphenyl ether, and iodine are mixed in a mass ratio of 1: (0.3-0.5): (20-30): (0.005-0.007), heated to 260-270°C for reaction for 1.5-2h, and after the reaction is completed, cooled to room temperature, filtered, washed with pure water 3-4 times, and vacuum dried at 50°C for 12h to obtain phenothiazine talc; phenothiazine talc, 1-iodoheptane, potassium tert-butoxide, and N,N-dimethylformamide are mixed in a mass ratio of 1: (0.5-0.7): (1.1-1.2): (20-30), stirred and reacted at 65-70°C for 2-3h, and after the reaction is completed, filtered, washed with pure water 3-4 times, and vacuum dried at 50°C for 12h to obtain heptane talc.
[0014] (4) weighing heptane talc and phosphorus oxychloride in a mass ratio of 1:(0.5-0.7); mixing heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection at 0°C, phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 were mixed for 30 minutes, and the heptane talc dispersion was added, and the reaction was carried out at 60-70°C for 12-14 hours. After the reaction was completed, Filter and wash with pure water for 3-4 times, and vacuum dry at 50°C for 12 hours to obtain aldehyded talc; mix aldehyded talc, trifluoromethylaniline, arginine, and methanol in a mass ratio of 1: (0.1-0.2): (0.5-0.7): (20-30), heat to 40-50°C and reflux for 2-3 hours, filter after the reaction, wash with pure water for 3-4 times, and vacuum dry at 50°C for 12 hours to obtain modified talc;
[0015] (5) The following raw materials are weighed: modified unsaturated polyester resin, dispersant, modified talc, bentonite, fumed silica, titanium dioxide, cobalt isooctanoate, cyclohexanone peroxide, and dibutyl phthalate, mixed and ground to a fineness of ≤30 μm, and irradiated under a 500 W high-pressure mercury lamp to obtain atomic putty for special body materials.
[0016] Preferably, the preparation method of the modified polysiloxane in step (2) is: octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, and trifluoropropyltrimethylcyclotrisiloxane are mixed in a mass ratio of 1: (0.8-1): (0.2-0.3), heated to 80-90° C. under nitrogen protection, stirred for 30-40 min, continued to heat to 110-120° C., added 0.02%-0.03% of the mass of octamethylcyclotetrasiloxane with a 25wt% tetramethylammonium hydroxide aqueous solution, and then added 3%-4% of the mass of octamethylcyclotetrasiloxane with 1,3-bis (4-hydroxybutyl) tetramethyldisiloxane, continued to stir for 3-4h, heated to 150° C., reacted for 3-4h, reduced pressure to 2-2.5KPa, and continued to react for 3-4h to obtain the modified polysiloxane.
[0017] Preferably, in step (2), the molar ratio of tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, trimethylolpropane diallyl ether, and hydroquinone is 1.2:1.2:1:0.8:0.2:0.2:0.04; the mass ratio of the modified unsaturated polyester resin precursor, modified polysiloxane, and tetrabutyl orthotitanate is 1:0.5:0.001; and the mass ratio of the pre-modified unsaturated resin and isocyanate terpyridine is 1:0.07.
[0018] Preferably, the preparation method of the pretreated talc in step (3) is: p-aminophenyltrimethoxysilane, anhydrous ethanol and pure water are mixed in a mass ratio of 1:10:10 for 10 minutes, talc powder with a mass of 0.5 times that of p-aminophenyltrimethoxysilane is added, the temperature is raised to 110°C, refluxed for 3-4 hours, filtered and washed with anhydrous ethanol 4 times, and vacuum dried to obtain p-aminophenyltrimethoxysilane-modified talc powder; p-aminophenyltrimethoxysilane-modified talc powder, chlorobenzene and dioxane are mixed in a mass ratio of 1:(2-3):(2.1-2.2):(10-12), the temperature is raised to 150-160°C for reaction for 3-4 hours, filtered and washed with pure water 3-4 times, and vacuum dried at 50°C for 12 hours to obtain the pretreated talc powder.
[0019] Preferably, the talc powder is obtained by mixing talc powder with a particle size of 1250 mesh and talc powder with a particle size of 800 mesh in a mass ratio of 1:2.
[0020] Preferably, the amount of the raw materials in step (5) is: by mass, 45-65 parts of modified unsaturated polyester resin, 1-3 parts of dispersant, 30-50 parts of modified talc, 1-2 parts of bentonite, 5-7 parts of fumed silica, 10-20 parts of titanium dioxide, 1-2 parts of cobalt isooctanoate, 10-20 parts of cyclohexanone peroxide, 1 part of diphenyliodonium hexafluorophosphate, and 25-35 parts of dibutyl phthalate.
[0021] Preferably, the dispersant in step (5) is BYK110; the bentonite mesh size is 200 mesh; the specific surface area of the fumed silica is 200 m2 / g; and the titanium dioxide is BR3662.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] When preparing the atomic putty for special vehicle body materials, the present invention comprises the following steps: firstly, reacting a modified unsaturated polyester resin precursor obtained by reacting tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol and hydroquinone with a hydroxyl-terminated modified polysiloxane, and then reacting with isocyanate-based terpyridine to obtain the modified unsaturated polyester resin; secondly, reacting talc powder modified with p-aminophenyltrimethoxysilane with chlorobenzene, cyclizing with sulfur powder, reacting with 1-iodoheptane, and then oxidizing with trichloride phosphorus oxychloride to graft p-trifluoromethylaniline and arginine to obtain the modified talc; and finally, mixing and grinding the modified unsaturated polyester resin, a dispersant, modified talc powder, bentonite, fumed silica, titanium dioxide, cobalt isooctanoate, cyclohexanone peroxide and dibutyl phthalate, and irradiating under a high-pressure mercury lamp to obtain the atomic putty for special vehicle body materials.
[0024] First, a modified unsaturated polyester resin precursor obtained by reacting tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol and hydroquinone is reacted with a hydroxyl-terminated modified polysiloxane, and then reacted with isocyanate-terminated terpyridine to obtain a modified unsaturated polyester resin; excessive acid is added during the synthesis of the modified unsaturated polyester resin precursor so that the modified unsaturated polyester resin precursor can be grafted with the hydroxyl-terminated modified polysiloxane; the side chain of the modified polysiloxane contains fluorine elements and double bonds, the presence of fluorine elements and polysiloxane can improve the heat resistance of the material, the double bonds can increase the unsaturation of the unsaturated polyester resin, increase the double bond content, form a denser cross-linking network in the subsequent curing process, and improve the mechanical properties and curing speed; the hydroxyl-terminated modified polysiloxane is then reacted with isocyanate-terminated terpyridine; an amide bond is generated by the reaction of a hydroxyl group and an isocyanate group, and the amide bond and terpyridine have good complexing ability with metals, which can improve the adhesion of the material to the metal substrate.
[0025] Secondly, the talc modified with p-aminophenyltrimethoxysilane is reacted with chlorobenzene. The surface of the talc modified with p-aminophenyltrimethoxysilane contains aminophenyl groups, which can be cyclized with sulfur powder to generate phenothiazine. The phenothiazine is then reacted with 1-iodoheptane to introduce a long hydrophobic chain of an alkane. After phosphorus oxychloride is aldehyded, p-trifluoromethylaniline and arginine are grafted through a Schiff base reaction to obtain the modified talc. Arginine, as an amphiphilic cationic group, can adsorb negatively charged bacteria through the attraction of positive and negative charges, and then pierce the bacterial cell membrane through the long hydrophobic chain of the alkane to achieve antibacterial properties. The phenothiazine group has good optical properties and contains It contains N and S heteroatoms and often acts as an electron donor. The C=N double bond of the Schiff base can play a similar role to the C=C double bond and can be used to construct a conjugated π skeleton structure. The trifluoromethyl structure of trifluoromethylaniline has a strong electron-withdrawing group. The phenothiazine group, carbon-nitrogen double bond, and trifluoromethylaniline constitute a D-π-A structure, which has good optical absorption properties in the visible light region. It can be constructed into a photoinitiator system with diphenyliodonium hexafluorophosphate. Under ultraviolet light irradiation, the phenyl radicals generated by photolysis can efficiently initiate free radical polymerization, thereby initiating the polymerization of unsaturated polyester resins, reducing the use of styrene crosslinkers and initiators, and increasing the curing speed. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The talc powder used in the following examples and comparative examples is obtained by mixing talc powder with a particle size of 1250 mesh and talc powder with a particle size of 800 mesh in a mass ratio of 1:2; the dispersant used is BYK110; the bentonite used has a mesh size of 200 mesh; the specific surface area of the fumed silica used is 200 m 2 / g; the titanium dioxide used is BR3662.
[0028] Embodiment 1:
[0029] A method for preparing atomic putty for special vehicle body materials, the method for preparing atomic putty for special vehicle body materials comprising the following preparation steps:
[0030] (1) Weigh bis(trichloromethyl) carbonate and 4-amino-2,2,6,2-terpyridine in a molar ratio of 1:3; mix bis(trichloromethyl) carbonate and chlorobenzene in a mass ratio of 1:10 to obtain a bis(trichloromethyl) carbonate solution, and stir at -5°C for 10 min; mix 4-amino-2,2,6,2-terpyridine and chlorobenzene in a mass ratio of 1:10 to obtain a 4-amino-2,2,6,2-terpyridine solution; dropwise add the 4-amino-2,2,6,2-terpyridine solution to the bis(trichloromethyl) carbonate solution at a dropping rate of 1 mL / min, and after the dropwise addition, keep the temperature at -5°C and stir for 30 min, heat to 70°C and reflux for reaction for 7 h, filter after the reaction, wash with chloroform 4 times, and vacuum dry at 50°C for 12 h to obtain isocyanate terpyridine;
[0031] (2) Octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and trifluoropropyltrimethylcyclotrisiloxane were mixed in a mass ratio of 1:0.8:0.2, heated to 90°C and stirred for 40 min under nitrogen protection, then heated to 120°C, 0.02% by weight of octamethylcyclotetrasiloxane of 25 wt% tetramethylammonium hydroxide aqueous solution was added, and then 3% by weight of octamethylcyclotetrasiloxane of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane was added and stirred for 4 h, then heated to 150°C and reacted for 4 h. h, reduce the pressure to 2.5 KPa, continue the reaction for 4 h to obtain modified polysiloxane; weigh tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, trimethylolpropane diallyl ether, and hydroquinone in a molar ratio of 1.2:1.2:1:0.8:0.2:0.2:0.04; mix tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, and hydroquinone, heat to 160°C, heat at a rate of 10°C / h to 190°C, react for 2 h, and then evacuate for 30 mi n, continue to react until the acid value is 60 mgKOH / g, cool to 160°C, add trimethylolpropane diallyl ether, react until the acid value is 40 mgKOH / g, and obtain a modified unsaturated polyester resin precursor; add modified polysiloxane and tetrabutyl orthotitanate to the modified unsaturated polyester resin precursor at a temperature of 160°C, the mass ratio of the modified unsaturated polyester resin precursor, the modified polysiloxane and the tetrabutyl orthotitanate is 1:0.5:0.001, heat to 170°C for reaction, and then heat at a speed of 10°C / h. The temperature was raised to 190°C, maintained at a vacuum degree of -0.085 MPa for 20 min, cooled to 60°C to obtain a pre-modified unsaturated polyester resin, the pre-modified unsaturated polyester resin and styrene were mixed at a mass ratio of 1:0.05, the temperature was raised to 70°C, isocyanate-based terpyridine was added, the mass ratio of the pre-modified unsaturated resin to isocyanate-based terpyridine was 1:0.07, the temperature was raised to 80°C to react for 2 h, ethylene glycol was added to continue the reaction for 30 min, and the unsaturated polyester resin was obtained after the reaction was completed;
[0032] (3) p-Aminophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed at a mass ratio of 1:10:10 for 10 minutes, talcum powder with a mass of 0.5 times that of p-aminophenyltrimethoxysilane was added, the temperature was raised to 110°C, refluxed for 4 hours, filtered and washed with anhydrous ethanol 4 times, and vacuum dried to obtain p-aminophenyltrimethoxysilane-modified talcum powder; p-Aminophenyltrimethoxysilane-modified talcum powder, chlorobenzene and dioxane were mixed at a mass ratio of 1:2:2.1:10, the temperature was raised to 160°C for 4 hours, filtered and washed with pure water 4 times, and vacuum dried at 50°C for 12 hours to obtain a prepreg Treating talcum powder; mixing pretreated talcum powder, sulfur powder, diphenyl ether, and iodine in a mass ratio of 1:0.3:20:0.005, heating to 270°C for reaction for 2 hours, cooling to room temperature after the reaction, filtering, washing with pure water 4 times, and vacuum drying at 50°C for 12 hours to obtain phenothiazine-based talcum powder; mixing phenothiazine-based talcum powder, 1-iodoheptane, potassium tert-butoxide, and N,N-dimethylformamide in a mass ratio of 1:0.5:1.1:20, stirring at 70°C for reaction for 3 hours, filtering, washing with pure water 4 times, and vacuum drying at 50°C for 12 hours to obtain heptane talcum powder,
[0033] (4) Weigh heptane talc and phosphorus oxychloride in a mass ratio of 1:0.5; mix heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection and at 0°C, mix phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 for 30 minutes, add the heptane talc dispersion, react at 70°C for 14 hours, filter and wash with pure water 4 times after the reaction, and vacuum dry at 50°C for 12 hours to obtain aldehyde-modified talc; mix aldehyde-modified talc, trifluoromethylaniline, arginine, and methanol in a mass ratio of 1:0.1:0.5:20, heat to 50°C and reflux for 3 hours, filter and wash with pure water 4 times after the reaction, and vacuum dry at 50°C for 12 hours to obtain modified talc;
[0034] (5) The following raw materials were weighed: 45 parts by mass of modified unsaturated polyester resin, 1 part of dispersant, 30 parts of modified talc, 1 part of bentonite, 5 parts of fumed silica, 10 parts of titanium dioxide, 1 part of cobalt isooctanoate, 10 parts of cyclohexanone peroxide, 1 part of diphenyliodonium hexafluorophosphate, and 25 parts of dibutyl phthalate. The above raw materials were mixed and ground to a fineness of 30 μm, and irradiated under a 500 W high-pressure mercury lamp to obtain atomic putty for special body materials.
[0035] Embodiment 2:
[0036] A method for preparing atomic putty for special vehicle body materials, the method for preparing atomic putty for special vehicle body materials comprising the following preparation steps:
[0037] (1) Weigh bis(trichloromethyl) carbonate and 4-amino-2,2,6,2-terpyridine in a molar ratio of 1:3; mix bis(trichloromethyl) carbonate and chlorobenzene in a mass ratio of 1:10 to obtain a bis(trichloromethyl) carbonate solution, and stir at -5°C for 7 minutes; mix 4-amino-2,2,6,2-terpyridine and chlorobenzene in a mass ratio of 1:10 to obtain a 4-amino-2,2,6,2-terpyridine solution; dropwise add the 4-amino-2,2,6,2-terpyridine solution to the bis(trichloromethyl) carbonate solution at a dropping rate of 1 mL / min, and after the dropwise addition, keep the temperature at -5°C and stir for 30 minutes, heat to 67°C and reflux for reaction for 6.5 hours, filter after the reaction, wash with chloroform 4 times, and vacuum dry at 50°C for 12 hours to obtain isocyanate terpyridine;
[0038] (2) Octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and trifluoropropyltrimethylcyclotrisiloxane were mixed in a mass ratio of 1:0.9:0.25, heated to 85°C and stirred for 35 min under nitrogen protection, then heated to 115°C, 0.02% by mass of octamethylcyclotetrasiloxane of 25 wt% tetramethylammonium hydroxide aqueous solution was added, and then 3% by mass of octamethylcyclotetrasiloxane of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane was added and stirred for 3.5 h, then heated to 150°C, and reacted. The mixture was heated to 160°C, and then heated at a rate of 10°C / h to 190°C. The mixture was reacted for 2h and then vacuumed for 3.5h to obtain a modified polysiloxane. Tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, trimethylolpropane diallyl ether and hydroquinone were weighed in a molar ratio of 1.2:1.2:1:0.8:0.2:0.2:0.04. Tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol and hydroquinone were mixed, and the mixture was heated to 160°C, and then heated at a rate of 10°C / h to 190°C. The mixture was reacted for 2h and then vacuumed for 3 hours. 0min, continue to react until the acid value is 60mgKOH / g, cool to 160℃, add trimethylolpropane diallyl ether, react until the acid value is 40mgKOH / g, and obtain a modified unsaturated polyester resin precursor; add modified polysiloxane and tetrabutyl orthotitanate to the modified unsaturated polyester resin precursor at a temperature of 160℃, the mass ratio of the modified unsaturated polyester resin precursor, modified polysiloxane and tetrabutyl orthotitanate is 1:0.5:0.001, heat to 170℃ for reaction, and then heat at 10℃ / h The temperature was raised at a rate of 1:0.05, and after the temperature was raised to 190°C, it was kept at a vacuum degree of -0.085MPa for 20min, and cooled to 60°C to obtain a pre-modified unsaturated polyester resin. The pre-modified unsaturated polyester resin and styrene were mixed at a mass ratio of 1:0.05, and the temperature was raised to 70°C. Isocyanate-based terpyridine was added, and the mass ratio of the pre-modified unsaturated resin to isocyanate-based terpyridine was 1:0.07. The temperature was raised to 80°C for reaction for 2h, and ethylene glycol was added to continue the reaction for 30min. After the reaction was completed, an unsaturated polyester resin was obtained;
[0039] (3) p-Aminophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed at a mass ratio of 1:10:10 for 10 minutes, talcum powder with a mass of 0.5 times that of p-aminophenyltrimethoxysilane was added, the temperature was raised to 110°C, refluxed for 3.5 hours, filtered and washed with anhydrous ethanol 4 times, and vacuum dried to obtain p-aminophenyltrimethoxysilane-modified talcum powder; p-Aminophenyltrimethoxysilane-modified talcum powder, chlorobenzene and dioxane were mixed at a mass ratio of 1:2.5:2.15:11, the temperature was raised to 155°C for reaction for 3.5 hours, filtered and washed with pure water 3 times, and vacuum dried at 50°C for 12 hours to obtain Pre-treat talc; mix pre-treated talc, sulfur powder, diphenyl ether, and iodine in a mass ratio of 1:0.4:25:0.006, heat to 265°C for reaction for 1.7 hours, cool to room temperature after the reaction, filter, wash with pure water three times, and vacuum dry at 50°C for 12 hours to obtain phenothiazine talc; mix phenothiazine talc, 1-iodoheptane, potassium tert-butoxide, and N,N-dimethylformamide in a mass ratio of 1:0.6:1.15:25, stir and react at 67°C for 2.5 hours, filter, wash with pure water three times, and vacuum dry at 50°C for 12 hours to obtain heptane talc.
[0040] (4) Weigh heptane talc and phosphorus oxychloride in a mass ratio of 1:0.6; mix heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection and at 0°C, mix phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 for 30 minutes, add the heptane talc dispersion, react at 65°C for 13 hours, filter and wash with pure water three times after the reaction, and vacuum dry at 50°C for 12 hours to obtain aldehyde-modified talc; mix aldehyde-modified talc, trifluoromethylaniline, arginine, and methanol in a mass ratio of 1:0.15:0.6:25, heat to 45°C and reflux for 2.5 hours, filter and wash with pure water three times after the reaction, and vacuum dry at 50°C for 12 hours to obtain modified talc;
[0041] (5) The following raw materials were weighed: 50 parts by mass of modified unsaturated polyester resin, 2 parts of dispersant, 42 parts of modified talc, 1 part of bentonite, 5.5 parts of fumed silica, 17 parts of titanium dioxide, 1.5 parts of cobalt isooctanoate, 17 parts of cyclohexanone peroxide, 1 part of diphenyliodonium hexafluorophosphate, and 30 parts of dibutyl phthalate. The above raw materials were mixed and ground to a fineness of 30 μm, and irradiated under a 500 W high-pressure mercury lamp to obtain atomic putty for special body materials.
[0042] Embodiment 3:
[0043] A method for preparing atomic putty for special vehicle body materials, the method for preparing atomic putty for special vehicle body materials comprising the following preparation steps:
[0044] (1) Weigh bis(trichloromethyl) carbonate and 4-amino-2,2,6,2-terpyridine in a molar ratio of 1:3; mix bis(trichloromethyl) carbonate and chlorobenzene in a mass ratio of 1:10 to obtain a bis(trichloromethyl) carbonate solution, and stir at -5°C for 5 minutes; mix 4-amino-2,2,6,2-terpyridine and chlorobenzene in a mass ratio of 1:10 to obtain a 4-amino-2,2,6,2-terpyridine solution; dropwise add the 4-amino-2,2,6,2-terpyridine solution to the bis(trichloromethyl) carbonate solution at a dropping rate of 1 mL / min, and after the dropwise addition, keep the temperature at -5°C and stir for 30 minutes, heat to 65°C and reflux for reaction for 6 hours, and after the reaction, filter and wash with chloroform 4 times, and vacuum dry at 50°C for 12 hours to obtain isocyanate terpyridine;
[0045] (2) Octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, and trifluoropropyltrimethylcyclotrisiloxane were mixed in a mass ratio of 1:1:0.3, heated to 80°C under nitrogen protection and stirred for 30 minutes, then heated to 110°C, 0.03% of the mass of octamethylcyclotetrasiloxane in a 25 wt% tetramethylammonium hydroxide aqueous solution was added, and then 4% of the mass of octamethylcyclotetrasiloxane in 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane was added and stirred for 4 hours, and then heated to 150°C and reacted for 3 hours. , reduce the pressure to 2KPa, continue to react for 3h to obtain modified polysiloxane; weigh tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, trimethylolpropane diallyl ether, and hydroquinone in a molar ratio of 1.2:1.2:1:0.8:0.2:0.2:0.04; mix tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, and hydroquinone, heat to 160°C, heat at a rate of 10°C / h to 190°C, react for 2h, and then evacuate for 30min, The reaction was continued until the acid value reached 60 mgKOH / g, the temperature was lowered to 160°C, trimethylolpropane diallyl ether was added, and the reaction was continued until the acid value reached 40 mgKOH / g to obtain a modified unsaturated polyester resin precursor; modified polysiloxane and tetrabutyl titanate were added to the modified unsaturated polyester resin precursor at a temperature of 160°C, the mass ratio of the modified unsaturated polyester resin precursor, the modified polysiloxane and the tetrabutyl titanate was 1:0.5:0.001, the temperature was raised to 170°C for reaction, and the reaction was continued at a rate of 10°C / h. The temperature was raised to 190° C., and then maintained at a vacuum degree of -0.085 MPa for 20 min, and then cooled to 60° C. to obtain a pre-modified unsaturated polyester resin, and the pre-modified unsaturated polyester resin and styrene were mixed at a mass ratio of 1:0.05, and then the temperature was raised to 70° C., and isocyanate-based terpyridine was added, and the mass ratio of the pre-modified unsaturated resin to isocyanate-based terpyridine was 1:0.07, and then the temperature was raised to 80° C. to react for 2 h, and ethylene glycol was added to continue the reaction for 30 min, and after the reaction, an unsaturated polyester resin was obtained;
[0046] (3) p-Aminophenyltrimethoxysilane, anhydrous ethanol, and pure water were mixed at a mass ratio of 1:10:10 for 10 minutes, talcum powder with a mass of 0.5 times that of p-aminophenyltrimethoxysilane was added, the temperature was raised to 110°C, refluxed for 3 hours, filtered, washed with anhydrous ethanol 4 times, and vacuum dried to obtain p-aminophenyltrimethoxysilane-modified talcum powder; p-Aminophenyltrimethoxysilane-modified talcum powder, chlorobenzene, and dioxane were mixed at a mass ratio of 1:3:2.2:12, the temperature was raised to 150°C for reaction for 3 hours, filtered, washed with pure water 3 times, and vacuum dried at 50°C for 12 hours to obtain pre-treated Pretreated talc; pretreated talc, sulfur powder, diphenyl ether, and iodine were mixed in a mass ratio of 1:0.5:30:0.007, heated to 260°C for reaction for 1.5 hours, cooled to room temperature after the reaction, filtered, washed with pure water 3 times, and vacuum dried at 50°C for 12 hours to obtain phenothiazine talc; phenothiazine talc, 1-iodoheptane, potassium tert-butoxide, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.7:1.2:30, stirred and reacted at 65°C for 2 hours, filtered, washed with pure water 3 times, and vacuum dried at 50°C for 12 hours to obtain heptane talc,
[0047] (4) Weigh heptane talc and phosphorus oxychloride in a mass ratio of 1:0.7; mix heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection and at 0°C, mix phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 for 30 minutes, add the heptane talc dispersion, react at 60°C for 12 hours, filter and wash with pure water three times after the reaction, and vacuum dry at 50°C for 12 hours to obtain aldehyde-modified talc; mix aldehyde-modified talc, trifluoromethylaniline, arginine, and methanol in a mass ratio of 1:0.2:0.7:30, heat to 40°C and reflux for 2 hours, filter and wash with pure water three times after the reaction, and vacuum dry at 50°C for 12 hours to obtain modified talc;
[0048] (5) The following raw materials were weighed: 65 parts by mass of modified unsaturated polyester resin, 3 parts of dispersant, 50 parts of modified talc, 2 parts of bentonite, 7 parts of fumed silica, 20 parts of titanium dioxide, 2 parts of cobalt isooctanoate, 20 parts of cyclohexanone peroxide, 1 part of diphenyliodonium hexafluorophosphate, and 35 parts of dibutyl phthalate. The raw materials were mixed and ground to a fineness of 30 μm, and irradiated under a 500 W high-pressure mercury lamp to obtain atomic putty for special vehicle body materials.
[0049] Comparative Example 1:
[0050] The difference between the preparation method of the putty for special vehicle body materials in Comparative Example 1 and Example 2 is that step (2) is modified as follows: tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, trimethylolpropane diallyl ether, and hydroquinone are weighed in a molar ratio of 1.2:1.2:1:0.8:0.2:0.2:0.04; tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, and hydroquinone are mixed and heated to After reaching 160°C, the temperature was increased at a rate of 10°C / h to 190°C, and after reacting for 2 hours, the mixture was vacuumized for 30 minutes. The reaction was continued until the acid value reached 60 mgKOH / g, the temperature was lowered to 160°C, trimethylolpropane diallyl ether was added, and the reaction was continued until the acid value reached 40 mgKOH / g to obtain a pre-modified unsaturated polyester resin. The pre-modified unsaturated polyester resin and styrene were mixed in a mass ratio of 1:0.05 to obtain an unsaturated polyester resin.
[0051] Comparative Example 2:
[0052] The difference between the preparation method of atomic putty for special vehicle body materials in Comparative Example 2 and Example 2 is that step (4) is modified as follows: weigh heptane talc and phosphorus oxychloride in a mass ratio of 1:0.6; mix heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection and at 0°C, phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 for 30 minutes, add the heptane talc dispersion, react at 65°C for 13 hours, filter and wash with pure water after the reaction, and vacuum dry at 50°C for 12 hours to obtain formaldehyde talc; mix formaldehyde talc, trifluoromethylaniline and methanol in a mass ratio of 1:0.15:25, heat to 45°C and reflux for 2.5 hours, filter and wash with pure water 3 times after the reaction, and vacuum dry at 50°C for 12 hours to obtain modified talc.
[0053] Comparative Example 3:
[0054] The difference between the preparation method of the putty for special vehicle body materials of Comparative Example 3 and Example 2 is that step (4) is modified as follows: weigh heptane talc and phosphorus oxychloride in a mass ratio of 1:0.6; mix heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection and at 0°C, mix phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 for 30 minutes, add the heptane talc dispersion, react at 65°C for 13 hours, filter and wash with pure water after the reaction, and vacuum dry at 50°C for 12 hours to obtain aldehyde talc; mix aldehyde talc, arginine and methanol in a mass ratio of 1:0.6:25, heat to 45°C and reflux for 2.5 hours, filter and wash with pure water 3 times after the reaction, and vacuum dry at 50°C for 12 hours to obtain modified talc;
[0055] Modify step (5) as follows: weigh the following raw materials: 50 parts by mass of modified unsaturated polyester resin, 2 parts of dispersant, 42 parts of modified talc, 1 part of bentonite, 5.5 parts of fumed silica, 17 parts of titanium dioxide, 1.5 parts of cobalt isooctanoate, 17 parts of cyclohexanone peroxide, and 30 parts of dibutyl phthalate; mix and grind the above raw materials to a fineness of ≤30 μm, and irradiate under a 500 W high-pressure mercury lamp to obtain atomic putty for special body materials.
[0056] Test example:
[0057] Test method: The examples and comparative examples were tested according to the standards in Table 1. The results are shown in Table 1.
[0058] Table 1 Test results statistics
[0059]
[0060]
[0061] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the putty for special vehicle body materials prepared by the present invention has good quick-drying, heat-resistant and antibacterial properties and good adhesion to metal substrates. The invention discloses that a modified unsaturated polyester resin precursor obtained by reacting tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol and hydroquinone is reacted with a modified polysiloxane terminated with a hydroxyl group, and then reacted with isocyanate-based terpyridine to obtain a modified unsaturated polyester resin; excessive acid is added during the synthesis of the modified unsaturated polyester resin precursor so that the modified unsaturated polyester resin precursor can be grafted with the modified polysiloxane terminated with a hydroxyl group; the side chain of the modified polysiloxane contains fluorine element and double bond, the presence of fluorine element and polysiloxane can improve the heat resistance of the material, the double bond can increase the unsaturation of the unsaturated polyester resin, increase the double bond content, form a denser cross-linking network in the subsequent curing process, and improve the mechanical properties and curing speed; the modified polysiloxane terminated with a hydroxyl group is reacted with isocyanate-based terpyridine; an amide bond is generated by the reaction of a hydroxyl group and an isocyanate group, and the amide bond and terpyridine have good complexing ability with metals, and can improve the adhesion of the material to the metal substrate.
[0062] Secondly, the talc modified with p-aminophenyltrimethoxysilane is reacted with chlorobenzene. The surface of the talc modified with p-aminophenyltrimethoxysilane contains aminophenyl groups, which can be cyclized with sulfur powder to generate phenothiazine. The phenothiazine is then reacted with 1-iodoheptane to introduce a long hydrophobic chain of an alkane. After phosphorus oxychloride is aldehyded, p-trifluoromethylaniline and arginine are grafted through a Schiff base reaction to obtain the modified talc. Arginine, as an amphiphilic cationic group, can adsorb negatively charged bacteria through the attraction of positive and negative charges, and then pierce the bacterial cell membrane through the long hydrophobic chain of the alkane to achieve antibacterial properties. The phenothiazine group has good optical properties and contains It contains N and S heteroatoms and often acts as an electron donor. The C=N double bond of the Schiff base can play a similar role to the C=C double bond and can be used to construct a conjugated π skeleton structure. The trifluoromethyl structure of trifluoromethylaniline has a strong electron-withdrawing group. The phenothiazine group, carbon-nitrogen double bond, and trifluoromethylaniline constitute a D-π-A structure, which has good optical absorption properties in the visible light region. It can be constructed into a photoinitiator system with diphenyliodonium hexafluorophosphate. Under ultraviolet light irradiation, the phenyl radicals generated by photolysis can efficiently initiate free radical polymerization, thereby initiating the polymerization of unsaturated polyester resins, reducing the use of styrene crosslinkers and initiators, and increasing the curing speed.
[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A putty for special car body materials, characterized in that: The putty for special vehicle body materials is obtained by mixing and grinding modified unsaturated polyester resin, dispersant, modified talc, bentonite, fumed silica, titanium dioxide, cobalt isooctanoate, cyclohexanone peroxide, and dibutyl phthalate, and then irradiating under a high-pressure mercury lamp; The modified unsaturated polyester resin is obtained by reacting a modified unsaturated polyester resin precursor obtained by reacting tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, and hydroquinone with a hydroxyl-terminated modified polysiloxane, and then reacting with isocyanate-based terpyridine; The modified talc is obtained by reacting talc modified with p-aminophenyltrimethoxysilane with chlorobenzene, cyclizing with sulfur powder, reacting with 1-iodoheptane, aldehydeizing with phosphorus oxychloride, and then grafting arginine.
2. A method for preparing putty for special vehicle body materials, characterized in that: The method comprises the following preparation steps: (1) Weighing bis(trichloromethyl) carbonate and 4-amino-2,2,6,2-terpyridine in a molar ratio of 1:3; mixing bis(trichloromethyl) carbonate and chlorobenzene in a mass ratio of 1:10 to obtain a bis(trichloromethyl) carbonate solution, and stirring at -5°C for 5-10 minutes; mixing 4-amino-2,2,6,2-terpyridine and chlorobenzene in a mass ratio of 1:10 to obtain a 4-amino-2,2,6,2-terpyridine solution; dropping the 4-amino-2,2,6,2-terpyridine solution into the bis(trichloromethyl) carbonate solution at a dropping rate of 1 mL / min, and stirring at -5°C for 30 minutes after the dropping, heating to 65-70°C and reflux reaction for 6-7 hours, and filtering after the reaction, washing with chloroform 4 times, and vacuum drying at 50°C for 12 hours to obtain isocyanate terpyridine; (2) Tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol and hydroquinone are mixed, heated to 160° C., then heated at a rate of 10° C. / h to 190° C., reacted for 2 hours, and then vacuumed for 30 minutes. The reaction was continued until the acid value reached 60 mgKOH / g, then the temperature was lowered to 160° C., trimethylolpropane diallyl ether was added, and the reaction was continued until the acid value reached 40 mgKOH / g to obtain a modified unsaturated polyester resin precursor; the modified unsaturated polyester resin precursor was added to the modified unsaturated polyester resin precursor at a temperature of 160° C. The pre-modified unsaturated polyester resin was prepared by heating the pre-modified unsaturated polyester resin and styrene in a mass ratio of 1:0.05, heating the pre-modified unsaturated polyester resin and adding isocyanate terpyridine, heating the pre-modified unsaturated polyester resin to 80°C for reaction for 2h, adding ethylene glycol for reaction for 30min, and obtaining the unsaturated polyester resin after the reaction. (3) Pretreated talc, sulfur powder, diphenyl ether, and iodine are mixed in a mass ratio of 1: (0.3-0.5): (20-30): (0.005-0.007), heated to 260-270°C for reaction for 1.5-2h, and after the reaction is completed, cooled to room temperature, filtered, washed with pure water 3-4 times, and vacuum dried at 50°C for 12h to obtain phenothiazine talc; phenothiazine talc, 1-iodoheptane, potassium tert-butoxide, and N,N-dimethylformamide are mixed in a mass ratio of 1: (0.5-0.7): (1.1-1.2): (20-30), stirred and reacted at 65-70°C for 2-3h, and after the reaction is completed, filtered, washed with pure water 3-4 times, and vacuum dried at 50°C for 12h to obtain heptane talc. (4) weighing heptane talc and phosphorus oxychloride in a mass ratio of 1:(0.5-0.7); mixing heptane talc and N,N-dimethylformamide in a mass ratio of 1:20 for 20 minutes to obtain a heptane talc dispersion; under nitrogen protection at 0°C, phosphorus oxychloride and N,N-dimethylformamide in a mass ratio of 1:10 were mixed for 30 minutes, and the heptane talc dispersion was added, and the reaction was carried out at 60-70°C for 12-14 hours. After the reaction was completed, Filter and wash with pure water for 3-4 times, and vacuum dry at 50°C for 12 hours to obtain aldehyded talc; mix aldehyded talc, trifluoromethylaniline, arginine, and methanol in a mass ratio of 1: (0.1-0.2): (0.5-0.7): (20-30), heat to 40-50°C and reflux for 2-3 hours, filter after the reaction, wash with pure water for 3-4 times, and vacuum dry at 50°C for 12 hours to obtain modified talc; (5) The following raw materials are weighed: modified unsaturated polyester resin, dispersant, modified talc, bentonite, fumed silica, titanium dioxide, cobalt isooctanoate, cyclohexanone peroxide, and dibutyl phthalate, mixed and ground to a fineness of ≤30 μm, and irradiated under a 500 W high-pressure mercury lamp to obtain atomic putty for special body materials.
3. The method for preparing putty for special vehicle body materials according to claim 2, characterized in that: The preparation method of the modified polysiloxane in step (2) is as follows: octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and trifluoropropyltrimethylcyclotrisiloxane are mixed in a mass ratio of 1:(0.8-1):(0.2-0.3), heated to 80-90° C. under nitrogen protection and stirred for 30-40 min, continued to heat to 110-120° C., added 0.02%-0.03% of the mass of octamethylcyclotetrasiloxane in a 25wt% tetramethylammonium hydroxide aqueous solution, and then added 3%-4% of the mass of octamethylcyclotetrasiloxane in 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane and continued to stir for 3-4h, heated to 150° C., reacted for 3-4h, reduced pressure to 2-2.5KPa, and continued to react for 3-4h to obtain the modified polysiloxane.
4. The method for preparing putty for special vehicle body materials according to claim 2, characterized in that: In step (2), the molar ratio of tetrahydrophthalic anhydride, fumaric acid, neopentyl glycol, diethylene glycol, ethylene glycol, trimethylolpropane diallyl ether, and hydroquinone is 1.2:1.2:1:0.8:0.2:0.2:0.04; the mass ratio of the modified unsaturated polyester resin precursor, modified polysiloxane, and tetrabutyl orthotitanate is 1:0.5:0.001; and the mass ratio of the pre-modified unsaturated resin and isocyanate terpyridine is 1:0.
07.
5. The method for preparing putty for special vehicle body materials according to claim 2, characterized in that: The preparation method of the pretreated talc powder in step (3) is as follows: p-aminophenyltrimethoxysilane, anhydrous ethanol and pure water are mixed in a mass ratio of 1:10:10 for 10 minutes, talc powder with a mass of 0.5 times that of p-aminophenyltrimethoxysilane is added, the temperature is raised to 110°C, refluxed for 3-4 hours, filtered and washed with anhydrous ethanol 4 times, and vacuum dried to obtain p-aminophenyltrimethoxysilane-modified talc powder; p-aminophenyltrimethoxysilane-modified talc powder, chlorobenzene and dioxane are mixed in a mass ratio of 1:(2-3):(2.1-2.2):(10-12), the temperature is raised to 150-160°C for reaction for 3-4 hours, filtered and washed with pure water 3-4 times, and vacuum dried at 50°C for 12 hours to obtain the pretreated talc powder.
6. The method for preparing putty for special vehicle body materials according to claim 5, characterized in that: The talcum powder is obtained by mixing talcum powder with a particle size of 1250 meshes and talcum powder with a particle size of 800 meshes in a mass ratio of 1:
2.
7. The method for preparing putty for special vehicle body materials according to claim 2, characterized in that: The amount of the raw materials used in step (5) is: by mass, 45-65 parts of modified unsaturated polyester resin, 1-3 parts of dispersant, 30-50 parts of modified talc, 1-2 parts of bentonite, 5-7 parts of fumed silica, 10-20 parts of titanium dioxide, 1-2 parts of cobalt isooctanoate, 10-20 parts of cyclohexanone peroxide, 1 part of diphenyliodonium hexafluorophosphate, and 25-35 parts of dibutyl phthalate.
8. The method for preparing putty for special vehicle body materials according to claim 2, characterized in that: The dispersant in step (5) is BYK110; the bentonite mesh size is 200 mesh; the specific surface area of the fumed silica is 200m 2 / g; the titanium dioxide is BR3662.
Citation Information
Patent Citations
Modified unsaturated polyester resin having excellent acid and alkali resistance, and preparation method thereof
CN106589749A
Spraying type putty as well as preparation method and application thereof
CN113512321A
Antibacterial plastic and preparation method thereof
CN117343372A
High-performance BPO cured putty and preparation method thereof
CN118126560A
Vapor putty for high-speed rail and preparation method thereof
CN118421128A
Cited By
High-end metal plate ash with good adhesion effect
CN120842896A